The spatial diffusion of a knowledge base: Laser technology research in West Germany, 1960-2005 - Michael Fritsch; Luis F. Medrano E. (European Regional Science Association (ERSA), 2010)
We analyze the spatial diffusion of laser-technology in Germany during the early phase of development, between 1960 and 2005. Research in this new technological field began in a few larger centers and then spread to other regions. In the early years, a large firm of the electronics industry located in Munich played a dominating role. The intraregional diffusion of the knowledge in laser technology was particularly high in those regions which have started laser research rather early. There is also no significant effect of regional knowledge in the field of laser technology on the number of regional laser-producers, what may be due to the rather early development stage of the system where not many producers entered the market. Mobility of persons as well as co-publications and co-patents between institutions played only a minor role in the period under investigation.
Keywords: L22; L69; R11; O52; 330; Innovation; regional innovation systems; knowledge; spatial diffusion; laser technology